2007
DOI: 10.1128/jvi.01847-06
|View full text |Cite
|
Sign up to set email alerts
|

CD8 T-Cell Recognition of Multiple Epitopes within Specific Gag Regions Is Associated with Maintenance of a Low Steady-State Viremia in Human Immunodeficiency Virus Type 1-Seropositive Patients

Abstract: The importance of HLA class I-restricted CD8 T-cell responses in the control of human immunodeficiency virus (HIV) infection is generally accepted. While several studies have shown an association of certain HLA class I alleles with slower disease progression, it is not fully established whether this effect is mediated by HIV-specific CD8 T-cell responses restricted by these alleles. In order to study the influence of the HLA class I alleles on the HIV-specific CD8 T-cell response and on viral control, we have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
150
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 139 publications
(169 citation statements)
references
References 34 publications
15
150
4
Order By: Relevance
“…Studies in chronic HIV infection have not been able to establish a relationship between overall breadth or magnitude of the IFN-c T-cell response to HIV and viral control (Addo et al, 2003;Masemola et al, 2004). With regard to the specificity of the response, only preferential targeting of Gag, and the breadth of the Gag response, has been correlated with superior viral control in large chronic HIV cohorts, as well as in elite controllers Geldmacher et al, 2007;Pereyra et al, 2008). How readily these lessons from chronic HIV infection should be applied to vaccine design and evaluation is not known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in chronic HIV infection have not been able to establish a relationship between overall breadth or magnitude of the IFN-c T-cell response to HIV and viral control (Addo et al, 2003;Masemola et al, 2004). With regard to the specificity of the response, only preferential targeting of Gag, and the breadth of the Gag response, has been correlated with superior viral control in large chronic HIV cohorts, as well as in elite controllers Geldmacher et al, 2007;Pereyra et al, 2008). How readily these lessons from chronic HIV infection should be applied to vaccine design and evaluation is not known.…”
Section: Discussionmentioning
confidence: 99%
“…These include preserved proliferative capacity (Day et al, 2007;Migueles et al, 2002;Rosenberg et al, 1997) and the ability to secrete multiple cytokines (CKs) (Betts et al, 2006;Harari et al, 2004;Kannanganat et al, 2007b). The specificity of the HIV proteins targeted by the T-cell response appears to be important, with a greater breadth of CD8 + epitopes targeted in Gag (Geldmacher et al, 2007;Kiepiela et al, 2007;Pereyra et al, 2008) or high-avidity CD8 + epitopes (Almeida et al, 2007) correlating with greater viral control. These and other features may be important attributes of a successful T-cell vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…Although the importance of CD8 T cells in controlling HIV replication is widely accepted, earlier reports have failed to show either a positive or negative correlation between viral load and the breadth or magnitude of CTL responses. Now it is known that Gag-specific responses are associated with low viremia (29,38,61), which can be explained by the capacity of Gag-specific CTLs to kill very recently infected cells, even before the viral genome integrates into the host genome (55). Also, it was shown that the functional profile of HIV-specific CD8 T cells in progressors is limited compared to that of nonprogressors, who consistently maintain highly functional CD8 T cells (12).…”
Section: Discussionmentioning
confidence: 99%
“…However, the predicted minimal epitope is in a different position in each peptide (i.e., it is offset). Therefore, we ascribe the lack of recognition of peptides NefBF 28 and NefBF 29 to the offsetting of the minimal epitope within those peptides. Similarly, we found that other reasons for nonrecognition were polymorphism within the optimal epitope (which may affect interaction to the T-cell receptor and thus effector response) and on epitope anchor positions.…”
Section: Study Subjectsmentioning
confidence: 99%
“…1,2 While several lines of evidence indicate that human immunodeficiency virus (HIV)-specific CD8 ϩ T cells are involved in the control of HIV replication, [3][4][5][6][7][8][9][10] several reports have focused on intrinsic defects in these cells to explain their failure to clear the virus, thereby leading to progression to acquired immunodeficiency syndrome (AIDS) in all infected individuals. [11][12][13][14] Similarly, simian immunodeficiency virus (SIV)-specific CD8 ϩ T cells contribute substantially to the partial control of viremia in rhesus macaques; depletion of CD8 ϩ T cells results in increased viremia in SIV-infected animals, 15,16 while viral escape at targeted epitopes accelerates disease progression and death in vaccinated animals.…”
Section: Introductionmentioning
confidence: 99%